Locus Control And Obedience in Covid-19 Prevention - Hariati Hariati; Friska Ernita Sitorus; Rostiodertina Girsang; Jon Piter Sinaga; Firdaus Fahdi (Program Studi Pendidikan Biologi, 2022)
Background: Locus control is dimensions psychology at play important in self elderly in application Covid-19 prevention. Purpose: for knowing knowing connection locus control to obedience elderly in doing protocol health Covid-19 prevention. Method : Study this is correlative . Research samples as many as 209 elderly with cluster sampling based on 5 villages and simple random sampling based on population data Study this will held in 1 year in Work Area Deli Tua Health Center . Instruments in the form of questionnaire locus control . Results: Research results obtained that there is connection locus control to obedience elderly in application proces Covid-19 prevention in the elderly. Conclusion: Importance observation to locus control To use increase obedience.